1996
DOI: 10.1097/00002820-199608000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Coping patterns among bone marrow transplant patients: a hermeneutical inquiry

Abstract: Bone marrow transplantation (BMT) has recently become the treatment of choice for a number of malignancies. This procedure is highly technical, involving the use of radiation and chemotherapy to destroy the patient's diseased bone marrow and with it functions of the entire immune system. It is a process with toxic effects that are experienced by all patients to varying degrees. A great deal of research related to the physiological aspects of this procedure has already been done, but considerably fewer studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 20 publications
2
18
0
1
Order By: Relevance
“…The effects of social isolation being both positive and negative is supported by a longitudinal study of BMT patients that found that time away from others was valued, yet at times, social contact was missed greatly. 29 This suggests that clinical judgment is required to determine support needed by patients at various times during treatment, especially as losses in confidence could potentially prevent patients from assertively expressing their need for support or time alone. It therefore could also be helpful to normalize variations in support needs and provide repeated opportunities for patients to indicate whether they are receiving their required level of support.…”
Section: Social Factors Affecting Adjustment To Appearance Changesvismentioning
confidence: 99%
“…The effects of social isolation being both positive and negative is supported by a longitudinal study of BMT patients that found that time away from others was valued, yet at times, social contact was missed greatly. 29 This suggests that clinical judgment is required to determine support needed by patients at various times during treatment, especially as losses in confidence could potentially prevent patients from assertively expressing their need for support or time alone. It therefore could also be helpful to normalize variations in support needs and provide repeated opportunities for patients to indicate whether they are receiving their required level of support.…”
Section: Social Factors Affecting Adjustment To Appearance Changesvismentioning
confidence: 99%
“…GVHD is a major determinant of the QoL of survivors. Chronic GVHD is most strongly correlated with worse QL after 6 months post transplantation This section reviews a qualitative study of patients undergoing allogeneic and autologous stem cell transplant in hospital (Shuster et al 1996), a personal account of the stem cell transplant experience (Morstyn 2009) and a descriptive longitudinal study (Schulmeister et al (2005) exploring patients' perceptions of QoL, quality of care and patient satisfaction whilst undergoing autologous SCT for a variety of conditions including haematological malignancy on an outpatient basis. The studies are summarised in Table 1.…”
Section: Andrykowski Et a 2005mentioning
confidence: 99%
“…The studies are summarised in Table 1. Shuster et al (1996) interviewed patients (n=11) during their hospitalisation for SCT including one who had an autologous and ten who had an allogeneic SCT. Informants were interviewed between one and four times a week whilst in hospital and once a week for four weeks post discharge.…”
Section: Andrykowski Et a 2005mentioning
confidence: 99%
See 2 more Smart Citations